The effectiveness of radiofrequency neurotomy of cervical facet in the treatment of secondary myofascial pain syndrome of neck and shoulder - Ismail, Mohd Nizamuddin (IIUM Press, International Islamic University Malaysia, 2017)
Myofascial pain syndrome (MPS) is a term to describe chronic regional pain syndrome, presented with hyperirritable spot called trigger points and/or tender spots that arises from taut band in a skeletal muscle. Muscle in general and myofascial pain in particular, has received less attention as major source of pain and dysfunction. Myofascial pain which is treatable, but often under-diagnosed and thereby under-treated due to lack of awareness among physician. In extreme situation, MPS can be mis-diagnosed as it may mimic other medical problems. The objectives of this study is to determine the prevalence of MPS of the neck and shoulder among cervical facet syndrome patients and to evaluate the effectiveness of radiofrequency neurotomy of the cervical facet in the treatment of secondary MPS of neck and shoulder. All patients who were diagnosed with cervical facet syndrome who presented to the pain clinic between October 2012 and February 2013 will be identified. Among these patients, those who had neck and shoulder pain symptoms will be further identified to evaluate the prevalence of these symptoms among cervical facet syndrome patients. Those with secondary MPS of neck and shoulder will undergo radiofrequency neurotomy of the cervical facet. Pain evaluation will be carried out using visual analogue pain score (VAS) with 0-10 cm score and also functional assessment using SF36 questionnaires at pre-procedure, 1st, 3rd and 6th month post procedure. The prevalence of secondary myofascial pain syndrome of neck and shoulder among cervical facet syndrome patients was 91.7%. There was a significant reduction of mean VAS with time (p < 0.001). There were significant mean differences only between pre-treatment and 1st month, pretreatment and 3rd month and pre-treatment and 6th month with percentage of reduction were 50%, 68.3% and 75% respectively. SF-36 questionnaire analysis showed an overall significant improvement with time (p <0.001) between pre-treatment and 1st month, pre-treatment and 3rd month and pre-treatment and 6th month for general health, limitation of activities, physical health, emotional health, social activities, energy and emotions, social activities 2 and general health 2 categories. The percentage of reductions between pre-treatment and 1st month, pretreatment and 3rd month and pre-treatment and 6th month were 70%, 80.6% and 82.9% respectively (general health), 70%, 85.6% and 87.1% respectively (limitation of activities), 78.8%, 88.6% and 89.4% respectively (physical health), 79.1%, 89.3% and 89.5% respectively (emotional health), 61.9%, 78.7% and 80.9% respectively (social activities), 56.2%, 69.3% and 71.4% respectively (energy and emotions), 59.3%, 67.6% and 70.1% respectively (social activities 2) and general health 2 category accounted for 58.8% and 65% each respectively. Pain assessment category showed significant mean reductions between pre-treatment and 1st month, pre-treatment and 3rd month, pre-treatment and 6th month as well as 1st and 3rd months and 1st and 6th months with percentage reductions of 55.2%, 68.7%, 69.6%, 13.5% and 14.5% respectively. In conclusion, the prevalence of secondary myofascial pain of the neck and shoulder was high among cervical facet syndrome patients in hospital University Sains Malaysia which was 91.7%. This study has proven that radiofrequency neurotomy of the cervical facet is very effective in the treatment of secondary myofascial pain syndrome of the neck and shoulder over the duration of 6 months.